Identification of linear DNA sequences that specifically bind the adeno-associated virus Rep protein. - McCarty, D M (1994)
We have used baculovirus-expressed Rep68 that has been purified to homogeneity to reexamine the binding properties of the Rep protein. We find that Rep68 is capable of binding to a linear DNA sequence that is contained within a 25-bp sequence of the A stem of the adeno-associated virus (AAV) terminal repeat proximal to the B and C palindromes. This has been shown conclusively by demonstrating that Rep68 could specifically bind to a synthetic oligonucleotide containing the 25-bp region in the absence of the other sequences within the terminal repeat. Rep78 was also capable of binding the A stem recognition element, as demonstrated by the fact that a DNA affinity column containing the 25-bp sequence can be used to purify Rep78. The ability to recognize the linear DNA sequence within the A stem provides a mechanism by which the Rep protein can be oriented on the terminal repeat so that only the correct strand is cut at the terminal resolution site (trs site) during terminal resolution. In addition, computer analysis suggests that sequences similar to the A stem element are present within the three AAV promoter regions. Electrophoretic mobility shift experiments clearly demonstrate that the p5 promoter contains a Rep binding sequence. DNase protection experiments indicate that the Rep binding sequence within the p5 promoter is located between the YY1 initiator sequence and the TATA binding site. This position immediately suggests a mechanism by which the Rep protein could act as a repressor or a transactivator of p5 transcription by interacting with either YY1 or TBP. In addition, gel shift experiments suggest that the p19 promoter also contains a Rep binding site. The presence of Rep binding sites upstream of both promoters suggests that these sites may be involved in coordinate regulation of AAV transcription. In addition, we have identified a heterologous Rep binding sequence within pBR322 DNA. A comparison of the sequences within the A stem, p5, and pBR322 binding sites suggests that a repeating GAGC motif is at least part of the Rep recognition sequence. In the accompanying report (D. M. McCarty, J. H. Ryan, S. Zolutukhin, X. Zhou, and N. Muzyczka, J. Virol. 68:4998-5006, 1994), we examine the relative affinity of Rep to the A stem site and the complete terminal repeat. Finally, we also have reexamined the ability of Rep68 and Rep78 to cut at the trs site in substrates that do not contain the B and C palindromes or any apparent secondary structure.(ABSTRACT TRUNCATED AT 400 WORDS)